Influence of body mass and environmental conditions on winter mortality risk of a northern ungulate: Evidence for a late‐winter survival bottleneck. Issue 3 (21st January 2020) - Kautz, Todd M.; Belant, Jerrold L.; Beyer, Dean E.; Strickland, Bronson K.; Duquette, Jared F.
Abstract: A relationship between winter weather and survival of northern ungulates has long been established, yet the possible roles of biological (e.g., nutritional status) and environmental (e.g., weather) conditions make it important to determine which potential limiting factors are most influential. Our objective was to examine the potential effects of individual (body mass and age) and extrinsic (winter severity and snowmelt conditions) factors on the magnitude and timing of mortality for adult (>2.5 years old) female white‐tailed deer ( Odocoileus virginianus [Zimmerman, 1780]) during February–May in the Upper Peninsula of Michigan, USA. One hundred and fifty deer were captured and monitored during 2009–2015 in two areas with varying snowfall. February–May survival ranged from 0.24 to 0.89 (mean = 0.69) across years. Mortality risk increased 1.9% with each unit increase in cumulative winter severity index, decreased 8.2% with each cumulative snow‐free day, and decreased 4.3% with each kg increase in body mass. Age and weekly snow depth did not influence weekly deer survival. Predation, primarily from coyote ( Canis latrans [Say, 1823]) and wolves ( Canis lupus [L., 1758]), accounted for 78% of known‐cause mortalities. Our results suggest that cumulative winter severity, and possibly to a lesser degree deer condition entering winter, impacted deer winter survival. However, the timing of spring snowmelt appeared to be the most influential factor determining late‐winter mortality of deer in our study. This supports the hypothesis that nutrition and energetic demands from weather conditions are both important to northern ungulate winter ecology. Under this model, a delay of several weeks in the timing of spring snowmelt could exert a large influence on deer survival, resulting in a survival bottleneck. Abstract : Northern ungulate population dynamics are correlated with winter weather patterns, and our goal was to evaluate when and why white‐tailed deer winter mortality occurs. We modeled weekly mortality risk of 150 adult female white‐tailed deer in Michigan in response to environmental and biological factors. The results suggested that body mass, severity of winter weather, and timing of spring snowmelt are influential on deer mortality, with the timing of snowmelt explaining the greatest amount of variation.